2014
DOI: 10.1007/s40615-014-0043-1
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Perceived Racism/Discrimination and Health Among Black American Women: a Review of the Literature from 2003 to 2013

Abstract: Objectives The purpose of this paper was to systematically review the literature investigating the relationship between perceived racism/discrimination and health among black American women. Methods Searches for empirical studies published from January 2003 to December 2013 were conducted using PubMed and PsycInfo. Articles were assessed for possible inclusion using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2009 framework. In addition, the Agency for Healthcare Research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(36 citation statements)
references
References 61 publications
0
36
0
Order By: Relevance
“…Between 1995 and 2006, the absolute prevalence of weight discrimination increased from 7 to 12 % in the USA, representing a 66 % increase in prevalence and exceeding the proportion that could be attributed to concomitant increases in obesity [9]. Despite the lay belief that weight stigma motivates positive behavioral change [10], most evidence demonstrates that weight shaming promotes poorer dietary and exercise practices and health care avoidance [11, 12], akin to how experienced racism correlates with negative health outcomes like cancer risk [13, 14]. As such, weight discrimination may contribute to obesity [3, 15] by discouraging individuals from seeking treatment, reducing engagement with social support, or promoting disordered eating patterns, less healthful food choices, and emotional dysregulation [12, 1621].…”
Section: Introductionmentioning
confidence: 99%
“…Between 1995 and 2006, the absolute prevalence of weight discrimination increased from 7 to 12 % in the USA, representing a 66 % increase in prevalence and exceeding the proportion that could be attributed to concomitant increases in obesity [9]. Despite the lay belief that weight stigma motivates positive behavioral change [10], most evidence demonstrates that weight shaming promotes poorer dietary and exercise practices and health care avoidance [11, 12], akin to how experienced racism correlates with negative health outcomes like cancer risk [13, 14]. As such, weight discrimination may contribute to obesity [3, 15] by discouraging individuals from seeking treatment, reducing engagement with social support, or promoting disordered eating patterns, less healthful food choices, and emotional dysregulation [12, 1621].…”
Section: Introductionmentioning
confidence: 99%
“…However, one study documented that self‐reported discrimination was associated with more severe coronary artery obstruction among veterans undergoing cardiac catherization, for blacks but not whites . A review of discrimination and physical health among black women found few significant associations for indicators of CVD, highlighting the need to better understand the conditions under which the stress of discrimination has adverse health effects …”
Section: Resultsmentioning
confidence: 99%
“…38 A review of discrimination and physical health among black women found few significant associations for indicators of CVD, highlighting the need to better understand the conditions under which the stress of discrimination has adverse health effects. 39 A 2017 review of 10 longitudinal studies found evidence of a consistent association between self-reported discrimination and body mass index (BMI), waist circumference, and incidence of obesity. 40 The associations between experiences of discrimination and adiposity were predominantly linear, and racial discrimination was also significantly associated with changes in BMI and waist circumference among women, but not men.…”
Section: Discrimination and Physical Healthmentioning
confidence: 99%
“…9,11 A systematic review of literature on perceived discrimination and health among Black women also found consistent evidence of an association between discrimination and adverse birth outcomes with several studies observing a doseresponse relationship. 10 Several pathways have been proposed linking discrimination to adverse birth outcomes. Racial and ethnic minority women have a higher lifetime exposure to chronic stress, which is a known risk factor for poor pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 99%